BRCA1, BRCA2 and PALB2 mutations and CHEK2 c.1100delC in different South African ethnic groups diagnosed with premenopausal and/or triple negative breast cancer. Issue 1 (December 2015) - Francies, F.; Wainstein, T.; De Leeneer, K.; Cairns, A.; Murdoch, M.; Nietz, S.; Cubasch, H.; Poppe, B.; Van Maerken, T.; Crombez, B.; Coene, I.; Kerr, R.; et al.
Abstract Background Current knowledge of the aetiology of hereditary breast cancer in the four main South African population groups (black, coloured, Indian and white) is limited. Risk assessments in the black, coloured and Indian population groups are challenging because of restricted information regarding the underlying genetic contributions to inherited breast cancer in these populations. We focused this study on premenopausal patients (diagnosed with breast cancer before the age of 50;n = 78) and triple negative breast cancer (TNBC) patients (n = 30) from the four South African ethnic groups. The aim of this study was to determine the frequency and spectrum of germline mutations inBRCA1, BRCA2 andPALB2 and to evaluate the presence of theCHEK2 c.1100delC allele in these patients. Methods In total, 108 South African breast cancer patients underwent mutation screening using a Next-Generation Sequencing (NGS) approach in combination with Multiplex Ligation-dependent Probe Amplification (MLPA) to detect large rearrangements inBRCA1 andBRCA2 . Results In 13 (12 %) patients a deleterious mutation inBRCA1 /2 was detected, three of which were novel mutations in black patients. None of the study participants was found to have an unequivocal pathogenic mutation inPALB2 . Two (white) patients tested positive for theCHEK2 c.1100delC mutation, however, one of these also carried a deleteriousBRCA2 mutation. Additionally, six variants of unknown clinical significance were identified (4 inBRCA2, 2 inPALB2 ), all in black patients. Within the group of TNBC patients, a higher mutation frequency was obtained (23.3 %; 7/30) than in the group of patients diagnosed before the age of 50 (7.7 %; 6/78). Conclusion This study highlights the importance of evaluating germline mutations in major breast cancer genes in all of the South African population groups. This NGS study shows that mutation analysis is warranted in South African patients with triple negative and/or in premenopausal breast cancer.